2018
DOI: 10.1101/499756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attention enhances LFP phase coherence in macaque visual cortex, improving sensory processing

Abstract: 24Attention selectively routes the most behaviorally relevant information among the vast 25 pool of sensory inputs through cortical regions. Previous studies have shown that visual 26 attention samples the surrounding stimuli periodically. However, the neural mechanism 27 underlying this sampling in the sensory cortex, and whether the brain actively uses these 28 rhythms, has remained elusive. Here, we hypothesize that selective attention controls the 29 phase of oscillatory synaptic activities to efficiently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
2
2
0
Order By: Relevance
“…We speculate that this finding is possibly due to the influence of a cognitive function like attention that enhances the non-linear synchronization between local neurons. Our hypothesis is in line with previous studies that have shown that spatial attention selectively increases the strength of synchronization between neurons processing the target stimulus (Womelsdorf et al, 2006;Zareian et al, 2018;Khamechian et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that this finding is possibly due to the influence of a cognitive function like attention that enhances the non-linear synchronization between local neurons. Our hypothesis is in line with previous studies that have shown that spatial attention selectively increases the strength of synchronization between neurons processing the target stimulus (Womelsdorf et al, 2006;Zareian et al, 2018;Khamechian et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found STN activ covaried with attentional fluctuation, too. ITPC in the STN during correct trials is significantly lo than during incorrect trials across theta, alpha, and beta bands, in line with previous brain-compu interface (BCI) paradigms in EEG (Zareian et al, 2020). The theta-BHG coupling in prefrontal regi and STN was also covaried with attentional fluctuation.…”
Section: Discussionsupporting
confidence: 87%
“…Some researchers investigate the effect of attention on inter-trial phase coherence at pre-stimulus low-frequency oscillations in area MT of monkey. Their results reveal that phase coherence in theta band increases when attention is deployed towards the receptive field of the recorded neuron (Zareian et al, 2020). In our study, we compared inter-trial phase coherence (ITPC) between the correct and incorrect trials in frontal regions and STN (Fig.…”
Section: Attention-related Neural Activity In Stnmentioning
confidence: 88%
“…Second, we show that on high behavioral performance epochs, LFP alpha coherency is higher than on low behavioral performance epochs. Signal coherency within and between brain areas is proposed as a key mechanism at the core of brain computing functions and supports information/stimulus processing(Fries, 2015b), accounting for network connectivity(Vinck et al, 2010), and changes in behavioral performance(Zareian et al, 2018, 2020). Last, we report changes in spike field coherency within the prefrontal cortex between the epochs of high vs. low behavioral performance, in the same frequency ranges as reported by others during attention orientation(Fries et al, 2008; Gregoriou et al, 2009b; Paneri and Gregoriou, 2017), thus pointing to a direct modulation of attentional mechanisms.…”
Section: Discussionmentioning
confidence: 99%